First Case of Mature Teratoma and Yolk Sac Testis Tumor Associated to Inherited MEN-1 Syndrome - Chiloiro, Sabrina (Front Endocrinol (Lausanne), 2019)
Introduction: Multiple endocrine neoplasia type 1 (MEN1) is an autosomal dominantly inherited endocrine tumor syndrome characterized by the development of cancer in various endocrine organs, particularly in the pituitary, parathyroid and pancreas. Moreover, in some cases, also non-endocrine tumors can be diagnosed, developing atypical phenotypes. Case report: We report herein the clinical history of a patient affected by MEN-1 syndrome who developed atypical features for this disease. The patient's clinical history started in August 2015 when he was referred, at the age of 23 years, to the Emergency Department of our Hospital for the occurrence of progressive asthenia, weakness, tremors and syncope. The biochemical test documented hyper-calcemia and severe hypoglycemia. The patient was referred to our Neuroendocrine Tumor and Pituitary Unit and he was diagnosed with pancreatic insulinoma, hypercalcemic hyperparathyroidism, and a prolactin secreting pituitary adenoma. The MEN-1 syndrome was suspected and genetic tests for mutation of menin resulted positive for the pathogenic variant c1548dupG. In January 2016, the patient was diagnosed with intratubular germ cell neoplasia, consisting of a mature teratoma and yolk sac tumor and he underwent a right orchiectomy. Conclusion: This is the first case report showing the clear association of MEN-1 syndrome with yolk sac tumors and teratomas, as in our case, the c1548dupG represents a pathogenic variant rather than a SNP. This case suggests the opportunity of an accurate evaluation of the testis particularly in young MEN-1 affected patients and that a prompt screening for neoplastic disease should involve all the endocrine glands.